Training on Therapeutic Communication and Patient Safety to Improve the Quality Indicator of Nursing Care at the Government Hospital in Bukittinggi, West Sumatera - Imelda Rahmayunia Kartika; Fitrianola Rezkiki; Sinta Wulandari; Rosi Okta Rida (CV. Media Digital Publikasi Indonesia, 2023)
Hospitals as one of the agencies that have a role in providing health services to the community are required to improve the quality of performance or quality of service in meeting needs and expectations so as to provide satisfaction to the community. One indicator of the quality service needed is an increase in the quality of services provided. As an effort to improve service quality, there are two quality indicators (communication and patient safety) that have not been optimally implemented in the hospitals. This Community Service (PKM) aims to provide training and increase knowledge through socialization and outreach to the nurses in one of the government hospitals in Bukittinggi, West Sumatera. The method that has been used in this PKM includes counseling related to the therapeutic communication between nurse-patient and socialization of hand washing with six steps and five moments. The results of this PKM obtained an increase in the knowledge and competence of nurses as well as the procedural for implementing hand washing and five moments in the treatment room. From the results of monitoring and evaluating PKM activities, it is known that nurses understand and practice therapeutic communication and five moments. It is hoped that this activity will be useful for increasing the knowledge and experience of therapeutic communication between nurses and patients as well as five moments of hand washing by nurses in the room as an effort to improve indicators of the quality of nursing care as a collaborative services in the hospital